Adaptation energy: Experimental evidence and applications in exercise science - Vasenina, E.; Kataoka, R.; Buckner, S. L. (Journal of Trainology, 2020)
Adaptation energy was proposed by Hans Selye as a working hypothesis to explain the exhaustion phase of the general adaptation syndrome (GAS), which resulted in loss of adaptation and death following exposure to various noxious agents (e.g., morphine, atropine, formaldehyde) in rodents. Despite being the mechanistic explanation behind his experimental findings, Selye was inconsistent in defining what "adaptation energy" was. Objective: To examine the evidence behind adaptation energy and the importance this concept has in the understanding of the GAS. In addition, we review relevant applications of adaptation energy in the understanding of adaptations to resistance exercise. Design & Methods: The experimental work of Hans Selye and sports science literature applying his findings was reviewed. Results/Conclusions: The concept of adaptation energy was mentioned in early publications linking Selye`s GAS to resistance exercise, however, modern applications appear to disregard his experiments (rodent studies) and his mechanistic explanations (adaptation energy). It seems unlikely that adaptation energy can explain adaptation and acute responses to exercise. Instead, the concept of adaptation energy appears to share similarities with some theories of aging. Overall, it is unclear if "adaptation energy" exists and if it warrants further discussion to help understand its application.